Thoracoscopic lobectomy versus open lobectomy in stage I non-small cell lung cancer: a meta-analysis. - Yi-xin Cai (PLoS ONE, 2013)
The objective of the present meta-analysis was to evaluate the survival, recurrence rate, and complications in patients with stage I non-small cell lung cancer (NSCLC) who received video-assisted thoracoscopic surgery (VATS) or open lobectomy. A literature search was conducted on June 31, 2012 using combinations of the search terms video-assisted thoracic surgery, open thoracotomy, lobectomy, and non-small-cell lung cancer (NSCLC). Inclusion criteria were: 1) Compared video-assisted thoracic surgery (VATS) lobectomy with open lobectomy. 2) Stage I NSCLC. 2) No previous treatment for lung cancer. 4) Outcome data included 5-year survival rate, complication, and recurrence rate. Tests of heterogeneity, sensitivity, and publication bias were performed. A total of 23 studies (21 retrospective and 2 prospective) met the inclusion criteria. VATS was associated with a longer 5-year survival (odds ratio [OR] = 1.622, 95% confidence interval [CI] 1.272 to 2.069; P<0.001), higher local recurrence rate (OR = 2.152, 95% CI 1.349 to 3.434; P = 0.001), similar distant recurrence rate (OR = 0.91, 95% CI 0.33 to 2.48; P = 0.8560), and lower total complication rate (OR = 0.45, 95% CI 0.24 to 0.84; P = 0.013) compared to open lobectomy. VATS was also associated with lower rates arrhythmias, prolonged air leakage, and pneumonia but it did not show any statistical significance. Patients with stage I NSCLC undergoing VATS lobectomy had longer survival and fewer complications than those who received open lobectomy.